Evaluating of a Super Bright LED as a Spectrophotometer Light Source at The Clinical Laboratory - Rangga Santoso; Dyah Titisari; Prastawa ATP; Her Gumiwang Ariswati; Nora Bouzeghaia (Department of Electromedical Engineering, POLTEKKES KEMENKES SURABAYA and IKATEMI, 2022)
Spectrophotometers generally use a halogen lamp as a light source that passes through a filter (wavelength) according to the material to be analyzed. This study aims to analyze the ability of the LED as a light source on a spectrophotometer. In this study, the authors have determined blood sugar parameters as the test material. So that the determination of the wavelength of the LED as a light source must be adjusted to the specifications of the wavelength in the reagent manual procedure used. In the BAV Greiner Glucose Reagent procedure, the allowable wavelength is between 500 - 570 nm with a cuvette thickness of 1 cm. Measured against the reagent blank by the endpoint method. From this reference, the author uses an LED light source with a wavelength of 530 nm, Epistar brand green. The module in this study consisted of a 530 nm LED lamp as a light source, then a lens was added to focus the light beam from the 530 nm LED. The author also adds a Slit / Aperture or it can be called a small hole so that the light passing through is focused at one point of the circle and is passed to the cuvette. The results of the absorption of light will be received by the light sensor (photoresistor) and the data is processed by Arduino and the results are displayed on the display. From the results of this study, the value ranges error from 1% to 3% when a comparative test is carried out with the Analyticon type Biolyzer100 spectrophotometer with 6 different samples and is repeated 5 times each. From these data, it is found that the LED with a wavelength of 530 nm is effective as a light source for checking blood sugar.